1986
DOI: 10.1111/j.1745-9125.1986.tb01497.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic Inequality and Levels of Homicide: An Analysis of Urban Neighborhoods*

Abstract: This paper presents an analysis of the relationship between levels of economic inequality and homicide rates for a sample of 26 neighborhoods in Manhattan, New York. It argues that neighborhoods are more appropriate units of analysis for studying inequality and homicide than are larger political and statistical units because neighborhoods are more likely to constitute meaningful frames of reference for social comparisons. The principle hypothesis is that a high degree of economic inequality in a neighborhood w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
1
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(107 citation statements)
references
References 19 publications
3
102
1
1
Order By: Relevance
“…CDs are well-defined units, each with an administrative community board, that as such have political and social a priori significance for their residents. (Messner and Tardiff, 1986;Marzuk et al, 1997;Suecoff et al, 1999;Galea et al, 2003a) Examples of these CDs include the Upper West Side in Manhattan and Bedford-Stuyvesant in Brooklyn. These CDs will be referred to as neighborhoods hereafter.…”
Section: Neighborhood Definitionmentioning
confidence: 99%
“…CDs are well-defined units, each with an administrative community board, that as such have political and social a priori significance for their residents. (Messner and Tardiff, 1986;Marzuk et al, 1997;Suecoff et al, 1999;Galea et al, 2003a) Examples of these CDs include the Upper West Side in Manhattan and Bedford-Stuyvesant in Brooklyn. These CDs will be referred to as neighborhoods hereafter.…”
Section: Neighborhood Definitionmentioning
confidence: 99%
“…For two early studies see Messner and Tardiff (1986) who studied 26 identified neighborhoods (somewhat larger than census tracts) in Manhattan, NY and Crutchfield (1989) who studied the effect of poverty and income inequality in Seattle census tracts. Hipp (2007) focused on income inequality in his study of crime in census tracts in 19 cities in 2000.…”
Section: Income Inequality and Crimementioning
confidence: 99%
“…Several studies (e.g. Crutchfield 1989;Hipp 2007;Mears and Bhati 2006;Messner and Tardiff 1986;Patterson 1991;Wang and Arnold 2008), have considered these issues at lower levels of analysis such as neighborhood clusters or census tracts. As elaborated further below, theory and some research evidence suggest that income levels and inequality within neighborhoods affect crime.…”
Section: Introductionmentioning
confidence: 99%
“…While a few studies have tested whether economic social distance (as measured by income or wealth inequality) affects crime rates (Crutchfield 1989;Hipp 2007b;Messner and Tardiff 1986), most studies have focused almost exclusively on the effect of racial/ethnic distance. Thus, studies have tested and found that racial/ethnic heterogeneity leads to more disorder (Connerly and Marans 1985;Hipp 2007a;Rountree and Warner 1999;Warner and Rountree 1997) or to higher crime rates (Hipp 2007b;Roncek and Maier 1991;Rountree and Warner 1999;Sampson and Groves 1989;Smith, Frazee, and Davison 2000;Warner and Rountree 1997).…”
Section: Effects Of Structural Social Distance On Micro-neighborhood-mentioning
confidence: 99%